Guinness World Records, 2016. Gamer's edition - Glenday, Craig (Guinness World Records Ltd., 2015)
Profiles video gaming systems and games from 2015, offering gaming records, lists of award-winning games, interviews with game designers and industry experts, key developments in gaming hardware, gaming tips and trivia, and more.